Gradenigo’s Syndrome: A Case Report (Bangladesh Journal of Neuroscience, 2014)
The syndrome of constant otorrhea, headache, diplopia and rarely ipsilateral Horner’s syndrome, which is attributed to inflammation of the petrous apex, is known as Gradenigo’s syndrome. We report a case of Gradenigo’s syndrome, which was 50 yrs old man who presented with 6 months history of left-sided headache, facial pain, diplopia and dropping of left eyelid. Examination demonstrated a left eye lateral gaze palsy, diplopia, and dropping of left eyelid, otoscopy revealed a congested left tympanic membrane. X-ray mastoid Townes view shows mastoid air cell are reduced on left side. CT scan study confirmed mastoid air cell are reduced and scleroses on left side and MRI shows T1 hypo & T2 & FLAIR hyperintense areas are on left mastoid region which consistent with Gradenigo’s Syndrome.Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 117-119